Acute Ascending Necrotizing Myelitis After COVID-19 Infection: A Clinicopathologic Report. Issue 3 (June 2022) - Guada, Luis; Cabrero, Franklyn Rocha; Baldwin, Nicole L.; Levi, Allan D.; Gultekin, Sakir H.; Verma, Ashok
Abstract : Objectives: Neurologic manifestations of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2, COVID-19) infection are common and varied. The objective of this report was to describe clinicopathologic findings of rare acute ascending necrotizing myelitis (ANM) and briefly summarize similar COVID-19–associated longitudinally extended transverse myelitis cases. Methods: We described the clinical presentation, disease course, diagnostic workup, therapeutic measures, and pathologic findings of ANM associated with COVID-19 infection. Results: A 31-year-old previously healthy woman developed a longitudinally extensive lower thoracic myelopathy 3 weeks after COVID-19 infection. The thoracic spinal cord lesion extended to cervical level in 1 week and to the lower medullary level in 2 more weeks. Thoracic laminectomy at T5-T6 level and cord biopsy revealed necrobiotic changes without viral particles or microglial nodules. The clinical deficit stabilized after immunomodulatory and eculizumab therapies. Discussion: COVID-19 infection can cause ANM. It adds to the spectrum of reported cases of COVID-19 –associated encephalitis and myelitis.